Research on cross-domain cooperation deployment of V2X infrastructure - Yuming GE; Qiqi MAO (Dianxin kexue)
Infrastructure is the foundation of the integration and innovative development of the vehicle to everything (V2X) industry.With the capabilities of reliable communication, accurate perception, and real-time computing, it supports the improvement of intelligent-connected vehicles, intelligent transportation and information and communication.On the basis of studying the scope and current situation of the new type V2X infrastructure, the challenges in cross-domain cooperation of it’s construction and service capability were analyzed.The framework of “physical separation and logic coordination” infrastructure architecture was proposed.Finally, the cross-domain cooperation of the new type V2X infrastructure at home and abroad was discussed, with corresponding development suggestions.